Giải thích các bước giải:
$\begin{array}{l}
a){x^2} + 3{y^2} + 2{z^2} - 2x + 12y + 4z + 15 = 0\\
\Rightarrow {x^2} - 2x + 1 + 3{y^2} + 12y + 12 + 2{z^2} + 4z + 2 = 0\\
\Rightarrow {\left( {x - 1} \right)^2} + 3\left( {{y^2} + 4y + 4} \right) + 2\left( {{z^2} + 2z + 1} \right) = 0\\
\Rightarrow {\left( {x - 1} \right)^2} + 3{\left( {y + 2} \right)^2} + 2{\left( {z + 1} \right)^2} = 0\\
\Rightarrow \left\{ \begin{array}{l}
x - 1 = 0\\
y + 2 = 0\\
z + 1 = 0
\end{array} \right. \Rightarrow \left\{ \begin{array}{l}
x = 1\\
y = - 2\\
z = - 1
\end{array} \right.
\end{array}$
bạn kiểm tra lại đề ý b nhé